استراتيجيات تعلّم مهارة الكلام لدارسي اللغة العربية في تركيا للمبتدئين / Strategies for learning speaking skill for Arabic language learners in Turkey for beginners - Ahmad Mohammad Atouf Aldershawi; Asem Ashehadeh Ali; Fahed Marmor; Mohammad Ahmad Alqudah, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2022)
مُلخَّص البحث: يعدّ الكلام المهارة الإنتاجية الأولى في مجال تعليم العربية، وقد أولى كثيرٌ من معلمي الجامعات والمعاهد اهتماماً كبيراً بتعليمها؛ لأنّهم يعدّونها في مرتبة متقدمة وسابقة على بقية المهارات، ويستدلّون على ذلك بأنّ الإنسان يتعلم في صغره الكلام من أبويه، قبل أن يتعلم مهارة الكتابة أو القراءة أو الاستماع، ويحتاج المعلم لتعليم مهارة الكلام إلى استراتيجيات مناسبة؛ لأنّ الاستراتيجية هي النمط العام للأنشطة التي يقوم المعلم والطلبة لإيجاد نشاط تعليمي ينشد الوصول إلى الهدف الذي تم تعيينه. ولتنمية هذه المهارة يستلزم إعداد برنامج مناسب وبتخطيط دقيق بغية تحقيق الأهداف المرجوة والمستمدة من أسس الحوار الفعّال، ومن أهداف تعليم اللغة العربية في مرحلة دراسية معينة، بحيث يشتمل البرنامج على صياغة الأهداف واختيار وتنظيم المحتوى وتحديد طرق التدريس والأنشطة والوسائل التعليمية والأساليب التقويمية المناسبة. وقد اتّبع الباحثان المنهج الوصفي التحليلي لجمع المادة وتحليلها. وقد توصل البحث إلى أنّ تنمية مهارة الكلام أو الحوار تستلزم إعداد برنامج مناسب ومخطط لتحقيق أهداف محددة مستمدة من أسس الحوار الفعال، ولتعليم اللغة العربية في مرحلة دراسية معينة، بحيث يشتمل البرنامج على صياغة الأهداف واختيار وتنظيم المحتوى وتحديد طرق التدريس والأنشطة والوسائل التعليمية والأساليب والتقويم المناسبة. الكلمات المفتاحية: استراتيجيات التعلّم، مهارة الكلام، دراسو العربية في تركيا. Abstract: Speaking is the first productive skill in the field of teaching Arabic, and many university and institute teachers have paid great attention to teaching it. Because they consider it an advanced rank and precedes the rest of the skills, and they infer that a person learns when he is young to speak from his parents, before he learns the skill of writing, reading or listening, and the teacher needs to teach the speaking skill to appropriate strategies; Because the strategy is the general pattern of activities that the teacher and students undertake to find an educational activity that seeks to reach the goal. To develop this skill, it is necessary to prepare an appropriate program and with careful planning to achieve the desired goals derived from the foundations of effective dialogue, and from the goals of teaching Arabic at a specific stage of study. The researchers followed the descriptive analytical method to collect and analyze the material. The research concluded that the development of speech or dialogue skill requires preparing an appropriate and planned program to achieve specific goals derived from the foundations of effective dialogue, and to teach the Arabic language at a certain stage of study, so that the program includes the formulation of goals, selection, and organization of content, and defining teaching methods, activities, teaching aids, and appropriate methods and evaluation. Keywords: learning strategies, speaking skill, Arabic studies in Turkey. Abstrak: Bertutur adalah kemahiran produktif pertama dalam bidang pengajaran bahasa Arab, dan ramai guru universiti dan institut memberi perhatian yang besar untuk mengajarnya. Kerana mereka menganggapnya sebagai pangkat lanjutan dan mendahului kemahiran yang lain, dan mereka menyimpulkan bahawa seseorang belajar semasa dia muda untuk bercakap daripada ibu bapanya, sebelum dia mempelajari kemahiran menulis, membaca atau mendengar, dan guru perlu mengajar kemahiran bertutur dengan strategi yang sesuai; Oleh kerana strategi adalah corak umum aktiviti yang dilakukan oleh guru dan pelajar untuk mencari sesuatu aktiviti pendidikan yang berusaha untuk mencapai matlamat. Untuk membangunkan kemahiran ini, adalah perlu untuk menyediakan program yang sesuai dan dengan perancangan yang teliti untuk mencapai matlamat yang diingini yang diperoleh daripada asas dialog yang berkesan, dan daripada matlamat pengajaran bahasa Arab pada peringkat pengajian tertentu. Pengkaji mengikuti kaedah analisis deskriptif untuk mengumpul dan menganalisis bahan. Penyelidikan menyimpulkan bahawa pembangunan kemahiran pertuturan atau dialog memerlukan penyediaan program yang sesuai dan terancang untuk mencapai matlamat khusus yang diperoleh daripada asas dialog yang berkesan, dan untuk mengajar bahasa Arab pada peringkat pengajian tertentu, supaya program itu termasuk perumusan. matlamat, pemilihan, dan organisasi kandungan, dan mentakrifkan kaedah pengajaran, aktiviti, alat bantu mengajar, dan kaedah serta penilaian yang sesuai. Kata kunci: strategi pembelajaran, kemahiran bertutur, pengajian bahasa Arab di Turki.